Molecular phylogenetic study and expression analysis of ATP-binding cassette transporter gene family in Oryza sativa in response to salt stress. (February 2015) - Saha, Jayita; Sengupta, Atreyee; Gupta, Kamala; Gupta, Bhaskar
Graphical abstract: Abstract: ATP-binding cassette (ABC) transporter is a large gene superfamily that utilizes the energy released from ATP hydrolysis for transporting myriad of substrates across the biological membranes. Although many investigations have been done on the structural and functional analysis of the ABC transporters in Oryza sativa, much less is known about molecular phylogenetic and global expression pattern of the complete ABC family in rice. In this study, we have carried out a comprehensive phylogenetic analysis constructing neighbor-joining and maximum-likelihood trees based on various statistical methods of different ABC protein subfamily of five plant lineages including Chlamydomonas reinhardtii (green algae), Physcomitrella patens (moss), Selaginella moellendorffii (lycophyte), Arabidopsis thaliana (dicot) and O. sativa (monocot) to explore the origin and evolutionary patterns of these ABC genes. We have identified several conserved motifs in nucleotide binding domain (NBD) of ABC proteins among all plant lineages during evolution. Amongst the different ABC protein subfamilies, 'ABCE' has not yet been identified in lower plant genomes (algae, moss and lycophytes). The result indicated that gene duplication and diversification process acted upon these genes as a major operative force creating new groups and subgroups and functional divergence during evolution. We have demonstrated that rice ABCI subfamily consists of only half size transporters that represented highly dynamic members showing maximum sequence variations among the other rice ABC subfamilies. The evolutionary and the expression analysis contribute to a deep insight into the evolution and diversity of rice ABC proteins and their roles in response to salt stress that facilitate our further understanding on rice ABC transporters.